Roseomonas fluvialis sp. nov., an aerobic bacteriochlorophyll a-containing freshwater bacterium isolated from river epilithic biofilm. Issue 3 (31st March 2023) - Hirose, Setsuko; Asano, Tomomi; Hamada, Moriyuki; Morohoshi, Sho; Kunihiro, Tadao; Hanada, Satoshi
Abstract : A strictly aerobic bacteriochlorophyll a -containing alphaproteobacterium, designated strain S08 T, was isolated from a biofilm sampled at Tama River in Japan. The non-motile and rod-shaped cells formed pink-beige pigmented colonies on agar plates containing organic compounds and showed in vivo absorption maxima at 798 and 866 nm in the near-infrared region, typical for the presence of bacteriochlorophyll a . The new bacterial isolate is Gram-negative, oxidase-negative and catalase-positive. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain S08 T was closely related to species in the genus Roseomonas . The closest phylogenetic relative of strain S08 T was Roseomonas lacus TH-G33 T (98.2 % sequence similarity). The major cellular fatty acids were C16 : 0, C18 : 1 2-OH and summed feature 8 (C18 : 1  ω 7 c /C18 : 1  ω 6 c ). The predominant respiratory quinone was ubiquinone-9. The major polar lipids contained diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylcholine and an aminolipid. The G+C content of the genomic DNA was 70.6 mol%. The average nucleotide identity and digital DNA–DNA hybridization values between strain S08 T and the related Roseomonas type strains were all far lower than the cut-off value for the delineation of species. The results of polyphasic comparisons showed that strain S08 T was clearly distinguishable from other members of the genus Roseomonas . Therefore, we propose a new species in the genus Roseomonas, namely, Roseomonas fluvialis sp. nov. The type strain is S08 T (=DSM 111902 T =NBRC 112025 T ).